2006
DOI: 10.1002/ajmg.a.31319
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postnatal findings in trisomy 17 mosaicism

Abstract: Trisomy 17 mosaicism is one of the rarest autosomal trisomies in humans. Thus far, only 23 cases have been described, most of them detected prenatally. In only five instances has mosaicism been demonstrated in lymphocytes and/or fibroblasts postnatally, and only in these have multiple congenital anomalies (MCA), facial dysmorphisms, and mental retardation been reported. Patients with trisomy 17 mosaicism at amniocentesis and a normal karyotype in blood and fibroblasts (n = 17) were always healthy. Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Ultrasonographic and pathological studies performed on fetuses with trisomy 13 revealed a severe compromise on brain, heart, and placenta as predicted by the EB model [29–31]. Likewise, fetuses and children with mosaic trisomy 17 showed delayed brain growth and/or cognitive function impairment in accordance to the in vitro model [11]. In view of the high correlation between the predicted alterations by the EB model, the teratoma model and the observations in patients, we can suggest that in vitro differentiation into EBs is a useful tool to study tissue alteration in aneuploidies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ultrasonographic and pathological studies performed on fetuses with trisomy 13 revealed a severe compromise on brain, heart, and placenta as predicted by the EB model [29–31]. Likewise, fetuses and children with mosaic trisomy 17 showed delayed brain growth and/or cognitive function impairment in accordance to the in vitro model [11]. In view of the high correlation between the predicted alterations by the EB model, the teratoma model and the observations in patients, we can suggest that in vitro differentiation into EBs is a useful tool to study tissue alteration in aneuploidies.…”
Section: Discussionmentioning
confidence: 94%
“…Complete trisomy 17 has never been reported in a live birth. In rare cases, a mosaic of normal euploid cells and cells with trisomy 17 are viable [11]. The patients carrying the trisomy have developmental delay and mental retardation along with multiple neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…If only a normal cell line is found on amniocentesis or cordocentesis, the question of UPD arises, but one has to keep in mind that mosaicism for some chromosomes (e.g. 17 and 20) might be found on CVS and/or amniocentesis, but not on cordocentesis, and the fetus might still be trisomic and clinically affected20. Testing for UPD is indicated if chromosome 14 or 15 is trisomic.…”
Section: Clinical Impactmentioning
confidence: 99%
“…However, the level of mosaicism varies greatly in different tissues and does not correlate with prognosis [11][12][13][14][15][16][17][18][19][20]. Molecular genetic analysis has confirmed mosaic T17 in several cases resulted from postzygotic mitotic errors in distribution of maternal chromosome 17 [13,16,18]. Parental origin of extra chromosome 17 was determined with genome-wide SNP-microarray molecular genetic analysis [11].…”
Section: Discussionmentioning
confidence: 99%